Lao People's Democratic Republic : Technical Assistance Report-Implementation of Risk Based Supervision. (IMF Staff Country Reports; Country Report, 2018)
The BoL has been implementing risk-based supervision (RBS) methods on a pilot basis. The RBS manual is now substantially complete, and the BSD staff are applying the RBS methods on a pilot basis. The BSD staff have drafted Institutional Profiles (IP) and Risk Assessment Summaries (RAS) for more than half of the banks; benchmarks and peer groups are being implemented; on-site reports of examination (ROX) have been utilized for several banks. The mission worked with off-site and on-site teams analyzing data for two pilot banks. Utilizing actual results for two pilot banks, the mission assisted BSD staff in identifying the risks, measuring and evaluating the impact on banks' condition, and formulating appropriate conclusions and ratings.